Increasing Student's Motivation in Learning English Using Duolingo - Ranti Maulya (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Motivating students is important to achieve the goals of the study. With high motivation, the students will study and learn the subject indeed. This study aims to verify the Duolingo application to increase students' learning motivation in English study. This research is focused on fraction materials studied by students in grade VIII SMPN 39 Takengon in the 2023-2024 academic year. This research method used is classroom qualitative research conducted in two meetings. The data analysis technique used is quantitative descriptive and qualitative descriptive analysis. Qualitative data were obtained from observations during the learning process while quantitative data were obtained from students' test results. The results showed an increase in learning motivation and learning outcomes of students in grade VIII SMPN 39 Takengon in English subject on fraction materials. The researcher concluded that learning using Duolingo application media was able to increase motivation and learning outcomes in English on fraction materials of students in grade VIII SMPN 39 Takengon.